Pengaturan Pengelolaan Kesehatan Lingkungan di Pasar Ikan Oeba Kelurahan Fatubesi Kecamatan Kota Lama Kota Kupang Ditinjau dari Peraturan Pemerintah Nomor 66 Tahun 2014 Tentang Kesehatan Lingkungan - Viorella Morentha; Hernimus Ratu Udju; Yosef Mario Monteiro (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
This study aims to find out and analyze the regulation of environmental health management in Oeba Fish Market, Fatubesi Village, Kota Lama District, Kupang City, reviewed from Government Regulation Number 66 of 2014 concerning Environmental Health. This study is an empirical legal research that uses primary data and secondary data collected using observation techniques, interviews and document studies that are analyzed in a qualitative descriptive jurificial manner where the data obtained is selected and arranged systematically, interpreted and presented in the form of descriptions. The results of the study show (1) The Regulation of Environmental Health Management by the Oeba Fishery Port at Oeba Fish Market, Fatubesi Village, Kota Lama District, Kupang City based on government regulation number 66 of 2014 concerning environmental health as found in the field has been running but is not optimal. (2) Inhibitory Factors in the Regulation of Environmental Health Management in Oeba Fish Market, Fatubesi Village, Kota Lama District, Kupang City, namely law enforcement factors, facilities and infrastructure factors, human resource factors and community knowledge factors that are still very low regarding Government Regulation Number 66 of 2014 concerning Environmental Health.